2007
DOI: 10.1016/s1001-0742(07)60044-8
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of particles, metal elements and natural organic matter in different water treatment processes

Abstract: Characterizing natural organic matter (NOM), particles and elements in different water treatment processes can give a useful information to optimize water treatment operations. In this article, transformations of particles, metal elements and NOM in a pilot-scale water treatment plant were investigated by laser light granularity system, particle counter, glass-fiber membrane filtration, inductively coupled plasma-optical emission spectroscopy, ultra filtration and resin absorbents fractionation. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…DOM is a heterogeneous mixture of various molecular weight aromatic and aliphatic organic compounds that contain oxygen, nitrogen, and sulfur functional groups (e.g., carboxyl, phenol, enol, alcohol, carbonyl, amine, and thiol) [1,2]. The properties of DOM strongly affect its reactivity in both natural and engineered aquatic systems [1,[3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…DOM is a heterogeneous mixture of various molecular weight aromatic and aliphatic organic compounds that contain oxygen, nitrogen, and sulfur functional groups (e.g., carboxyl, phenol, enol, alcohol, carbonyl, amine, and thiol) [1,2]. The properties of DOM strongly affect its reactivity in both natural and engineered aquatic systems [1,[3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is composed of relatively high apparent molecular weight (AMW) humic and fulvic acids, as well as low AMW proteins, organic acids, carbohydrates and other compounds (Leenheer and Croue, 2003). The molecular properties of DOM, notably its molecular weight, strongly affect its reactivity in both natural and engineered aquatic systems (Amy et al, 1987;Her et al, 2002a;Leenheer and Croue, 2003;Yan et al, 2006Yan et al, , 2007Korshin et al, 2009). High-performance liquid chromatographysize exclusion chromatography (HPLC-SEC) is one of the most widely used techniques to characterize DOM due to its important advantages, such as little need for DOM pre-concentration, small injection volume, and ease and speed of analysis (Chin et al, 1994;Her, 2003;Korshin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The results of pilot-scale tests with AlCl 3 , PACl and HPAC were compared with the traditional coagulation strategy (a composite coagulant prepared using Tests at pilot-scale and at full-scale have shown that particles and NOM are removed synergistically with HPAC as coagulant by sequential treatment processes including pre-ozonation, coagulation, flotation and sand filtration [6,8,20]. The residual Al is relatively low [21]. Coagulant optimization such as by HPAC application can be considered as an alternative option to enhance NOM removal from high alkalinity and micro-polluted waters.…”
Section: Coagulant Optimizationmentioning
confidence: 99%